A Comparison of Methodologies to Investigate the Influence of Light on the Atmosphere of a Space. Issue 3 (3rd July 2018) - Stokkermans, Mariska; Vogels, Ingrid; de Kort, Yvonne; Heynderickx, Ingrid
ABSTRACT: The impression of a space depends highly on the illumination in the space, which usually is a combination of electric light and daylight. In the present study, we compared three methodologies to study the influence of electric light and daylight on the perception of the light and the perception of the atmosphere of the space. In two experiments, rating scales were used (with a blocked and a random design, respectively) and in a third experiment the paired-comparison method was used to evaluate the light and the atmosphere of the space. In all experiments, visualizations were used to create differently illuminated spaces. All methodologies showed similar effects of daylight and electric light, which attests to the convergent validity of the research methods. However, the methodologies revealed different effect sizes, rendering the paired-comparison design most sensitive to detect the smallest differences. The results also allowed us to explore the contribution of electric light and daylight in creating an atmosphere. The use of visualizations enabled us to control the luminance of daylight and to disentangle the effects of daylight entering a window from the view from a window. The outcomes show that daylight plays a smaller role than electric light on the perception of light and atmosphere in a space when the luminance of daylight is controlled and there is no view outside.